Potential wildlife sentinels for monitoring the endemic spread of human buruli ulcer in South-East australia. - Connor Carson; Caroline J Lavender; Kathrine A Handasyde; Carolyn R O'Brien; Nick Hewitt; Paul D R Johnson; Janet A M Fyfe (Public Library of Science (PLoS), 2014)
The last 20 years has seen a significant series of outbreaks of Buruli/Bairnsdale Ulcer (BU), caused by Mycobacterium ulcerans, in temperate south-eastern Australia (state of Victoria). Here, the prevailing view of M. ulcerans as an aquatic pathogen has been questioned by recent research identifying native wildlife as potential terrestrial reservoirs of infection; specifically, tree-dwelling common ringtail and brushtail possums. In that previous work, sampling of environmental possum faeces detected a high prevalence of M. ulcerans DNA in established endemic areas for human BU on the Bellarine Peninsula, compared with non-endemic areas. Here, we report research from an emergent BU focus recently identified on the Mornington Peninsula, confirming associations between human BU and the presence of the aetiological agent in possum faeces, detected by real-time PCR targeting M. ulcerans IS2404, IS2606 and KR. Mycobacterium ulcerans DNA was detected in 20/216 (9.3%) ground collected ringtail possum faecal samples and 4/6 (66.6%) brushtail possum faecal samples. The distribution of the PCR positive possum faecal samples and human BU cases was highly focal: there was a significant non-random cluster of 16 M. ulcerans positive possum faecal sample points detected by spatial scan statistics (P<0.0001) within a circle of radius 0.42 km, within which were located the addresses of 6/12 human cases reported from the area to date; moreover, the highest sample PCR signal strength (equivalent to ≥10(6) organisms per gram of faeces) was found in a sample point located within this cluster radius. Corresponding faecal samples collected from closely adjacent BU-free areas were predominantly negative. Possums may be useful sentinels to predict endemic spread of human BU in Victoria, for public health planning. Further research is needed to establish whether spatial associations represent evidence of direct or indirect transmission between possums and humans, and the mechanism by which this may occur.